Konsep Tetandingan Jaje Sarad Pulagembal Sebagai Seni Lukis - Adi Udyana, I Made; Muka, I Ketut; Ruta, Made (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2022)
Jaje Sarad Pulagembal is one of the complementary facilities for the ceremony that attracts the attention of many people, not only the Balinese Hindu community, but also the wider community. In addition to being quite large, it also looks beautiful because it is arranged very artistically. Jaje Sarad Pulagembal is usually displayed in the courtyard of the temple, but not many people know what the purpose and meaning of Jaje Sarad is. Jaje Sarad is usually made during the implementation of the Madyaning Utama piodalan and above, namely the piodalan that uses bebangkit and the ceremony that uses Pulagembal. The method of creation is a systematic way of creating works of art. The stages of creating a work of art that outlines the design of the process of creating a work of art in accordance with the stages of creation from inspiration (ideas), design, to embodiment. How to realize an idea into a painting, of course, is not necessarily done without preparation. Preparation in this process can be divided into 5 stages of creation: (1) preparation, (2) elaboration, (3) synthesis, (4) concept realization, (5) completion or evaluation. In the title chosen, namely "Jaje Sarad Pulagembal's Counter-Concept as Painting", the concept is meant to be defined by various theoretical concepts that include ideas, designs, and the formation of art in general. Here it refers to the basic nature of art, namely composition, form, and color. Sarad is a Hindu religious ceremony in Bali which is mostly made of snacks made from rice flour with visualization of symbols of the contents of the universe. Pulagembal is a collection of several Bantenese that accompany several kojong fruit containing several types of sacred Banten snacks. Jaje Sarad Pulagembal is deemed appropriate to represent various images of life that is felt by the author, by forming new objects into jaje Sarad and not referring to the previous forms of jaje Sarad, the author can pour ideas and new forms into the painting. Not only a description of the author's life, but also raises environmental issues related to the ecology of the Balinese people.